2019
DOI: 10.26905/jkdp.v23i3.3157
|View full text |Cite
|
Sign up to set email alerts
|

The determinant factors of efficiency on Islamic banking and conventional banking in Indonesia

Abstract: As intermediary institutions, conventional banks have larger amount of loans to third party funds than of Sharia banks. Thus, the bank needs a performance appraisal to measure banking operations through efficiency. We examine the efficiency of Islamic banks and conventional banks in Indonesia and analyzes the factors that influence the level of efficiency known as the Two-Stage Data Envelopment Analysis method. We found that there are significant efficiency differences between Islamic banking and conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
1
6
0
7
Order By: Relevance
“…Credit risks in those contracts are in the form of the inability of the debtor to fulfill the obligation to the bank on the maturity dates and it will have an impact on the loss of Islamic banks (Al-Wesabi & Ahmad, 2013). According to Majdina, Munandar, & Effendi (2019), Islamic banks should manage the strategy of funds' distribution to improve their performance. Mokni et al (2014) who summarize some previous studies about the types of risks that dominate the banking industry, state that the ability to analyze credit risk will affect the ability of the Islamic bank to manage risk efficiently.…”
Section: Figure 2 the Proportion Of Financing In Islamic Banksmentioning
confidence: 99%
See 1 more Smart Citation
“…Credit risks in those contracts are in the form of the inability of the debtor to fulfill the obligation to the bank on the maturity dates and it will have an impact on the loss of Islamic banks (Al-Wesabi & Ahmad, 2013). According to Majdina, Munandar, & Effendi (2019), Islamic banks should manage the strategy of funds' distribution to improve their performance. Mokni et al (2014) who summarize some previous studies about the types of risks that dominate the banking industry, state that the ability to analyze credit risk will affect the ability of the Islamic bank to manage risk efficiently.…”
Section: Figure 2 the Proportion Of Financing In Islamic Banksmentioning
confidence: 99%
“…Further, Soekapdjo et al (2018) state that the higher NPF of Indonesian Islamic banks because of the new operational experience of Islamic banks and the limited ability of employees in the financing distribution. Majdina, Munandar, & Effendi (2019) state that Islamic banks may face potential losses due to high NPF and it can impact on the bad performance of Islamic banks. The performance of the bank to manage the NPF will influence the overall financial performance of Islamic banks.…”
Section: Introductionmentioning
confidence: 99%
“…On another hand, some empirical literature indicates that the Islamic banks' stability is worse than conventional banks because moral hazard and asymmetric information bear on the profit-and-loss sharing system (Kabir, Worthington, & Gupta, 2015;Lassoued, 2018). Volume 24, Issue 1, January 2020: 40-52 | 42 | 2016; Setyawati et al 2017;Sriyana, 2015;Widarjono, 2018;Risfandy, 2018;Octavio & Soesetio, 2019), efficiency of Islamic banks (Hosen & Rahmawati 2016;Aisyah & Hosen, 2018;Majdina, Munandar, & Effendi, 2019) and credit risk of Islamic banks (Firmansyah, 2015;Husa & Trinarningsih, 2015;Nugraheni & Muhammad, 2019). Our present study examines Islamic banks' financial stability in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, Pramuka (2011) found that an Islamic bank with a "full-fledged" scheme was more efficient than another one with an "Islamic window" scheme. Majdina et al (2019) found a significant difference in efficiency in IBs and CBs: ROA had a significant positive impact on CBs" efficiency, while CAR had a significant positive effect on IBs".…”
Section: Efficiencymentioning
confidence: 83%